PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN PELANGGAN DI HOLLAND BAKERY BATAM - Gultom, Rada Yusni Lestari; Mardika, Nanda Harry (SCIENTIA JOURNAL, 2019)
In an increasingly modern world demands entrepreneurs engaged in retail to compete in providing excellent service in order to increase customer satisfaction, besides that promotion is one strategy for companies to increase long-term profit. This study aims to determine the effect of service quality and promotion on customer satisfaction at Holland Bakkery batu aji Fanindo Batam. The population in this study were customers who had made purchases at Holland Bakery Batam. This research is a causal associative study using a quantitative approach. Sampling was taken using the incidental sampling method with an error rate of 5% so that a sample of 186 respondents could be drawn. Research data obtained from the results of questionnaires to respondents. Data analysis in this study used multiple linear regression analysis. The results of the analysis show that service quality variables affect customer satisfaction, this can be proven by the results of the t test which shows tcount> t table, while the promotion variable does not affect customer satisfaction. This can be proven in the previous test where tcount <t table and the value is significant. The results of the F test analysis show that service quality and promotion simultaneously have a significant effect on customer satisfaction at Holland Bakery Batam. This can be proven from the results of the F test (simultaneous) by showing the value F (F count)> (Ftable). And the value is significant. The conclusion of this study is that there is a positive and significant influence on the X1 variable on the Y variable, and there is no influence between X2 variables on the Y variable and there is a significant effect between the two X variables simultaneously on the Y variable.